2016
DOI: 10.1002/adhm.201600134
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Migration and Differentiation of Human Mesenchymal Stem Cells on Five‐Layered Collagenous Electrospun Scaffold Mimicking Native Cartilage Structure

Abstract: Cartilage degeneration is the major cause of chronic pain, lost mobility, and reduced quality of life for over estimated 150 million osteoarthritis sufferers worldwide. Despite intensive research, none of the available therapies can restore the hyaline cartilage surface beyond just fibrous repair. To overcome these limitations, numerous cell-based approaches for cartilage repair are being explored that aim to provide an appropriate microenvironment for chondrocyte maintenance and differentiation of multipotent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Deep porosities after decellularization could possibly provide a 3D micro pools hosting more cells [33,35] and may act to protect seeded cells from environmental disturbances such as medium changes. The importance of surface geometry and collagen architecture in cellular attachment, integration, migration and differentiation have been documented by several studies [22,24] . Although we could not perform various decellularization methods to examine their effects on surface geometry and subsequently on cell seeding, the obtained results highlight topographical parameters as a pivotal factor in decellularization methods of the BP and in vivo application of the BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep porosities after decellularization could possibly provide a 3D micro pools hosting more cells [33,35] and may act to protect seeded cells from environmental disturbances such as medium changes. The importance of surface geometry and collagen architecture in cellular attachment, integration, migration and differentiation have been documented by several studies [22,24] . Although we could not perform various decellularization methods to examine their effects on surface geometry and subsequently on cell seeding, the obtained results highlight topographical parameters as a pivotal factor in decellularization methods of the BP and in vivo application of the BP.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major components of the BP tissue is type I collagen networks embedded in extracellular matrix(ECM) which in turn determine antigenicity, structure-function properties and even recellularization potential [7,20,21] . Studies have revealed that cell migration and proliferation are influenced by collagen fibers density, spatial arrangement and porosity [22,24] . It has been recently shown that decellularization processes brings about extensive cellular membrane destruction and collagen fibers disruption in BP [25] .…”
Section: Introductionmentioning
confidence: 99%
“…It indicated that the hybrid scaffolds did not affect viability and bioactivity of ACs, as evidenced by the live/dead assay (82%) and positive staining for type II collagen and GAG after in vitro and in vivo experiments. On the other hand, Reboredo et al [179] used electrospinning to obtain hybrid scaffolds with the structure mimicking native cartilage tissues; the scaffolds had five layers, 1st and 5th layers included type I collagen nanofibers aligned randomly, 2nd and 4th layers consisted of mixture of type I and II collagen nanofibers, and 3rd layer of aligned type II collagen nanofibers (Fig. 10D).…”
Section: Collagen Denaturation In Blending Strategymentioning
confidence: 99%
“…Tremendous effort has been focused on this critical unmet need in orthopedics and significant progress has been made in laboratory and preclinical studies using cell-based, tissue engineering, growth factordriven, gene therapy, and bioprinting strategies. 5,15,49,[142][143][144][145][146][147][148][149][150][151][152][153][154][155][156] Yet, to date, there are no successful cartilage regeneration techniques available for use in humans. 18 The scientific, regulatory, financial, and clinical requirements for use of cartilage regeneration techniques in patients are extremely challenging, such that near-term solutions cannot be expected.…”
Section: Cartilage Regenerationmentioning
confidence: 99%